Post -1974 Greek Foreign Policy - Veremis, Thanos (Études helléniques / Hellenic Studies, 1997)
Greek foreign policy after the fall of the military regime can be classified within two periods, before and after the demise of communism in eastern Europe and the Soviet Union. Both Karamanlis and Papandreou represent a departure from Greece’s post-war identification with western policies and institutions. The former initiated a process of multilateralism in the communist Balkans and the latter pursued third world affiliations throughout his first term in power. Closer relations with the EU obliged Papandreou to make an about face turn in his policy vis-à-vis the Est, but the European Union’s failure to face the Yugoslav crisis in unison and develop a common foreign and security policy accounts for Greece’s swing towards the US. Greece’s relations with its Balkan neighbors improved after a period of tension with FYROM and Albania, but Turkey remains the most pressing security consideration of the Greek government.